Crash [videorecording (DVD)] - Haggis, Paul; Bullock, Sandra; Cheadle, Don; Dillon, Matt; Esposito, Jennifer, 1973-; Fichtner, William; Fraser, Brendan, 1968-; Isham, Mark (Artisan Home Entertainment, 2005)
A car accident brings together a group of strangers in Los Angeles. Crash takes a provocative, unflinching look at the complexities of racial tolerance in contemporary America.